The impact of unregulated ionic clay rare earth mining in China - Packey, Daniel J.; Kingsnorth, D. (Pergamon Press, 2016)
The ionic clay rare earth resources in China are the cheapest and most accessible source of heavy rare earths. They are also the most valuable. The Chinese rare earth market has an uncontrolled illegal market segment that represents approximately 40% of the domestic market, which translates to 30% of the global market. This sector of the market pays little or no attention to the environmental damage of their mining and processing actions and, through their unregulated supply, depresses the market price such that external (and in some cases, internal) producers are having difficulties making or maintaining profit margins. It creates significant negative externalities that adversely affects the native environment and the international rare earth market.